Uncovering the fungus responsible for stem and root rot of false indigo pathogen identification, new disease description, and genome analyses - Harrigian, Fiona (Plant disease, 2024)
Calonectria spp. can cause destructive diseases on forestry crops, legumes like soybean and peanut, and ornamentals. Species of Calonectria affecting ornamental plants are not well characterized or understood, though they have been widely documented as an issue in the ornamental industry. This research focused on the molecular identification, pathogenicity validation, and genome analysis of a Calonectria sp. isolate recovered from ornamental blue false indigo (Baptisia australis) plants showing disease symptoms of crown and root rot in a commercial nursery in Virginia. The fungus on B. australis was identified as C. fujianensis (Nectriaceae, Hypocreales), a member of the C. colhuonii species complex using multilocus sequencing. Pathogenicity tests were fulfilled by inoculating C. fujianensis conidia on B. australis seedlings, confirming a causal relationship between this pathogen and the disease symptoms observed. A 62.7 Mb high-quality hybrid genome assembly generated using Illumina and Nanopore data was obtained, contained in 16 contigs, four of which were complete chromosomes. A total of 750 effectors were found in the genome, similar to cutinase and pectinase virulence factors described from other Calonectria species' genomes. Characterization of this novel disease of B. australis advances our understanding of Calonectria as an important but poorly studied group of plant pathogens